Risk Identification and Assessment in Drinking Water Supply System in Taleghan Using the Failure Modes and Effects Analysis Method in 2020 - Hossein Masoumbeigi; Mehdi Sadat Rasul; Ghader Ghanizadeh (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: The importance of drinking water resources and their infrastructure for human health has made these resources one of the most vulnerable targets of terrorist attacks. The present study aimed to identify and assess the risks posed to drinking water facilities in Taleghan, Iran, using the failure modes and effects analysis(FMEA) method. Methods: This descriptive-analytical study was conducted in all water facilities in Taleghan, Iran, in 2020. The types of potential hazards and threats of water facilities were identified by reviewing the necessary documents, field visits, observation, interviews, and opinion polls of water supply experts in Alborz province. Thereafter, risk assessment was performed, risks were prioritized, and necessary solutions to reduce the risks were presented using the FMEA technique. Results: The present study identified 40 potential risks. The majority of risks belonged to water wells (37.5%). The identified risks were 7.5%, 40%, and 52.5%, respectively, related to the quantity, quality, as well as exploitation and maintenance of water facilities. The highest risk priority number were 576, 392, and 343, respectively, related to the critical threats caused by point source pollution around water wells, poor protection and security of the pumping station,  as well as fluctuations in water flow in the distribution network and reservoirs. Furthermore, 42.5, 35, and 22.5% of the risks were at the critical, moderate, and non-critical levels. Conclusion: Ad evidenced by the obtained results, water infrastructure in terms of exploitation and maintenance in the supply, treatment, and distribution sectors is vulnerable to various identified threats; therefore, it is necessary to make the needed adjustments based on the set priorities to prevent possible incidents.